Analysis Acceptance of XYZ Company Digital Membership Using Technology Acceptance Model - Skynyrd; Suwarno (International Journal Software Engineering and Computer Science (IJSECS), 2025)
The current study explores the acceptance of XYZ Company’s digital membership program in the light of the Technology Acceptance Model (TAM). The objective is to find some key values that predict user adoption, focusing mainly on the predictors of Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) in behavioral intention (BI). Data was collected from 378 respondents and Structural Equation Modeling (SEM) was used on the data obtained. The data provides evidence for the significant effects of PU and PEOU on BI as expected, underlining how important these constructions are to influence user acceptance. The study extends the TAM with other variables such as Trust, data privacy, and user experience (UX) to provide a broader understanding. These variables are important, especially in the case of a digital membership program operated by a company, for the technological requirements that need to satisfy multiple customers and match those needs with industry constraints. The study findings reveal a significant mediating effect of UX on the relationship between PEOU and PU, as well as a moderating impact of trust and data privacy on the relationship between PEOU and PU, which in turn creates a more satisfying level of assurance and satisfaction. While the findings inform, in a very specific way what Company XYZ can do from a management perspective to improve the user experience and enhance the benefits of its digital membership program and user adoption/engagement. In line with the academic literature, this study places TAM into the context of corporate digital membership offering relevant knowledge and practical recommendations for organizations to replicate similar initiatives. The strategic implications of these results demonstrate the importance for companies to design their digital solutions according to user expectations and needs, to consistently deliver optimal customer value and satisfaction in a highly competitive sales environment.